Evaluation and validation of portable NIRS to estimate in situ nutritional quality of Megathyrsus maximus population in breeding program at CIAT - Mazabel, Johanna; Hincapie, Alexander; Hernández, Luis Miguel; Arango, Jacobo; Jauregui, Rosa (Bioversity International and the International Center for Tropical Agriculture, 2022)
In breeding program at Alliance Bioversity international & CIAT we evaluate continually Hybrids or determinate nutritional quality. Many populations are selected for major nutritional characteristics like contents of protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF) and In vitro Digestibility (IVDM). The parameters relationate with quality are very important in selection process for identify promise genotypes. This process must be to quickly and technology Near infrared reflectance spectroscopy (NIRS) is a good tool rapid, low-cost, and used successfully for determination of chemical composition in forage grasses.